Hardware and software development for robocup SSL robots - Esen, Huzeyfe. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2013)
In Small Size League (SSL) which is one of the most dynamic and fastest competitions of RoboCup, a soccer game is played between two autonomous teams of 6 robots on a field of size 6050 mm 4050 mm. Because of this challenging feature of SSL, the robots should be controlled precisely so that they can react in real-time with intelligent soccer-like moves. In this thesis, we not only focus on the electronic board design of the robots, but also introduce new low and high level control algorithms that enable the robots to compete in SSL successfully. In the new electronic board that controls the main functions of the robot, the microcontroller MC9S08DZ128 and encoders with higher resolution have been utilized for precise control and the features of the motor driver MC33035 have been adapted accordingly. Morover, a new kicker circuit is designed so that the capacitors can be charged in a shorter amount of time. The algorithmic contributions of this thesis include not only a new low level control algorithm to drive brushless DC motors, but also implementation of the extended rapidly exploring random trees (ERRT) algorithm in our system for path planning and obstacle avoidance. Morover, new formation control algorithms have been developed for coordination of the robots. In this context, a Kalman filter is implemented to compansate for vision based system delay and least squares techniques are used to predict the ball position.
Keywords: Robotics.